2018
DOI: 10.1186/s12974-018-1183-8
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-5′-nucleotidase (CD73) attenuates inflammation after spinal cord injury by promoting macrophages/microglia M2 polarization in mice

Abstract: BackgroundImmune activation, specifically activation of macrophages and resident microglia, leading to inflammation is a key component in the progression of spinal cord injury (SCI). Macrophages/microglia exist in two states—the classically activated M1 phenotype that confers pro-inflammatory effects or the alternatively activated M2 phenotype that confers anti-inflammatory effects. Ecto-5′-nucleotidase (CD73) is an immunosuppressive molecule intricately involved in adaptive and innate immune responses and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 57 publications
4
58
0
Order By: Relevance
“…12,17 To evaluate the pro-inflammatory microenvironment after SCI, we detected the levels of TNF-α, IL-β and IL-6 in injured spinal cord. 17,20 To test BRD4 activation in microglia after SCI, we collected the T7-T10 level around the lesion part of the spinal cord to detect the gross level of BRD4 in the spinal cord. It is reported that BRD4 is implicated with pro-inflammatory phenotypes in various cell types and microglia play a critical role in inflammatory response in the central nervous system.…”
Section: Post-traumatic Inflammation Activates Brd4 In Microglia Cementioning
confidence: 99%
See 1 more Smart Citation
“…12,17 To evaluate the pro-inflammatory microenvironment after SCI, we detected the levels of TNF-α, IL-β and IL-6 in injured spinal cord. 17,20 To test BRD4 activation in microglia after SCI, we collected the T7-T10 level around the lesion part of the spinal cord to detect the gross level of BRD4 in the spinal cord. It is reported that BRD4 is implicated with pro-inflammatory phenotypes in various cell types and microglia play a critical role in inflammatory response in the central nervous system.…”
Section: Post-traumatic Inflammation Activates Brd4 In Microglia Cementioning
confidence: 99%
“…It is reported that BRD4 is implicated with pro-inflammatory phenotypes in various cell types and microglia play a critical role in inflammatory response in the central nervous system. 17,20 To test BRD4 activation in microglia after SCI, we collected the T7-T10 level around the lesion part of the spinal cord to detect the gross level of BRD4 in the spinal cord. Despite the sudden reduction at 1 hour after SCI, the level of BRD4 was increased after 1 hour of SCI, coinciding with the gradually elevated production of pro-inflammatory cytokines at the early stage of SCI, which indicated that BRD4 might be enhanced in microglia and induced inflammatory response after SCI ( Figure 1D,E).…”
Section: Post-traumatic Inflammation Activates Brd4 In Microglia Cementioning
confidence: 99%
“…play key roles in both time and space in the physiological microenvironment. 15 Increasing numbers of studies have shown that macrophages have different polarization states in different environments. M1 macrophages promote the secretion of proinflammatory factors and are neurotoxic, whereas M2 macrophages can suppress the inflammatory reaction and promote axonal growth.…”
Section: Macrophagesmentioning
confidence: 99%
“…As in therapeutic interventions for many diseases, G protein‐coupled receptors (GPCRs) appear as potential targets to skew microglial phenotype. Recent results suggest an important potential of microglial adenosine receptors in neuroprotection because expression of CD73, the ectoenzyme that produces extracellular adenosine, attenuates inflammation by promoting M2 polarization (Xu et al, ). Among the four subtypes of adenosine receptors, the A 2A is the most promising in neuroprotection (see (Franco & Navarro, ) for review).…”
Section: Introductionmentioning
confidence: 99%